2006
DOI: 10.4161/cc.5.9.2722
|View full text |Cite
|
Sign up to set email alerts
|

ATR-Chk1 Axis Protects BCR/ABL Leukemia Cells from the Lethal Effect of DNA Double-Strand Breaks

Abstract: BCR/ABL-positive leukemia cells accumulated more replication-dependent DNA doublestrand breaks (DSBs) than normal counterparts after treatment with cisplatin and mitomycin C (MMC, as assessed by pulse field gel electrophoresis (PFGE) and neutral comet assay. In addition, leukemia cells could repair these lesions more efficiently than normal cells and eventually survive genotoxic treatment. Elevated levels of drug-induced DSBs in leukemia cells were associated with higher activity of ATR kinase, and enhanced ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 72 publications
4
51
2
Order By: Relevance
“…Therefore, additional genetic aberrations accumulated during the course of CML may be promoted by BCR-ABL1 kinase and also by a preexisting abnormality responsible for the formation of t(9;22)(q34;q11). The former statement is supported by reports that BCR-ABL1 kinase-positive cells acquire more oxidative DNA lesions than normal counterparts in response to endogenous ROS and genotoxic treatment (109,110) and that BCR-ABL1 can inhibit some DNA repair mechanisms (MMR) and stimulate other mechanisms (NER, HRR, NHEJ, and SSA) at the cost of their fidelity (136) (Figure 3). However, the latter speculation about preexisting abnormality cannot be ruled out because chromosome abnormalities were detected in t(9;22)(q34;q11)-negative metaphases appearing during imatinib therapy in patients with newly diagnosed CML-CP (121).…”
Section: Consequences Of Genomic Instability In CMLsupporting
confidence: 57%
“…Therefore, additional genetic aberrations accumulated during the course of CML may be promoted by BCR-ABL1 kinase and also by a preexisting abnormality responsible for the formation of t(9;22)(q34;q11). The former statement is supported by reports that BCR-ABL1 kinase-positive cells acquire more oxidative DNA lesions than normal counterparts in response to endogenous ROS and genotoxic treatment (109,110) and that BCR-ABL1 can inhibit some DNA repair mechanisms (MMR) and stimulate other mechanisms (NER, HRR, NHEJ, and SSA) at the cost of their fidelity (136) (Figure 3). However, the latter speculation about preexisting abnormality cannot be ruled out because chromosome abnormalities were detected in t(9;22)(q34;q11)-negative metaphases appearing during imatinib therapy in patients with newly diagnosed CML-CP (121).…”
Section: Consequences Of Genomic Instability In CMLsupporting
confidence: 57%
“…5,11 Therefore, additional chromosomal aberrations accumulated during the course of CML may be promoted by preexisting condition responsible for t(9;22) and/or by BCR/ABL. The latter statement is supported by reports that BCR/ABL-positive cells acquire more DSBs than Figure 1 Representative examples of SKY analyses of chromosomal aberrations described in Table 1 Letters to the Editor normal counterparts in response to endogenous reactive oxygen species (ROS) and genotoxic treatment [12][13][14][15] and that BCR/ABL stimulates the efficiency but decreases the fidelity of DSB repair mechanisms. 13,16,17 However, the former speculation cannot be ruled out because chromosome abnormalities were detected in t(9;22)-negative metaphases appearing during imatinib therapy in patients with newly diagnosed CML-CP.…”
Section: T and T T And T Per Metaphasesupporting
confidence: 53%
“…Cell cycle checkpoints are responsible for the mediation of phase transitions, activation of repair mechanisms and the movement of DNA repair proteins to lesion sites. Studies from our lab, as well as others, have implicated that cells transformed by BCR/ABL-related FTKs exhibit extended activation of the S and G 2 /M cell cycle phase checkpoints when exposed to chemotherapeutic drugs and g-radiation (Bedi et al, 1995;Slupianek et al, 2002;Nieborowska-Skorska et al, 2006). We have recently reported that BCR/ABL leukemia cells might display enhanced stimulation of the ATR-Chk1 axis, which plays an important role in the activation of intra-Sphase checkpoint and drug resistance (NieborowskaSkorska et al, 2006).…”
Section: Checkpoint Activationmentioning
confidence: 79%
“…Drug resistance BCR/ABL and related FTKs such as TEL/ABL TEL/ PDGFbR, TEL/JAK2 and NPM/ALK demonstrate an enhanced ability to survive genotoxic stress probably owing to enhanced DNA repair, prolonged S and G 2 /M checkpoints for extended repair and inhibition of proapoptotic pathways (Bedi et al, 1995;AmaranteMendes et al, 1998;Skorski, 2002;Slupianek et al, 2002Slupianek et al, , 2006Canitrot et al, 2003;Lauren et al, 2003;Nieborowska-Skorska et al, 2006) (Figure 3). These three factors may work in concert to provide the necessary protection from DNA damage-induced apoptosis.…”
Section: Consequences Of Ftks Expressionmentioning
confidence: 99%